PTU-055 A Comparison Of Radiological And Endoscopic Oesophageal Stent Placement In Malignancy. (9th June 2014) - Chapman, T; Tyrell, H; Al-Hassani, H; Colcer, A; Bruce, A; Rajoriya, N; Warakaulle, D; Gorard, D; Sekhar, R
Abstract : Introduction: Self expanding metallic stent (SEMS) placement effectively palliates malignant dysphagia, most commonly due to oesophageal cancer. Typically stents are placed under fluoroscopic guidance, but some centres use direct vision endoscopy as an alternative. 1 There are however little data comparing the two techniques. At our 2-hospital institution, all patients presenting to Stoke Mandeville Hospital undergo radiologically guided stent placement, while patients at Wycombe Hospital undergo endoscopic placement without fluoroscopy. We describe our experience over a three year period. Methods: A retrospective observational study of all patients who underwent SEMS placement at our two hospitals over a three year period (2009–2012) was performed. 41 patients were included in the study, with placement of 48 SEMS. Improvement in dysphagia, survival and complication rates were the main outcome measures. Results: 21 patients underwent radiologically guided placement, 20 for oesophageal cancer, 14 male, median age 78 years. 20 patients underwent endoscopically guided placement, 17 for oesophageal cancer, 8 male, median age 80.5 years. Disease stage was similar in both groups, with metastases in 11/21 of the radiology group, and 10/20 of the endoscopy group. More patients in the radiology group had received prior radiotherapy (13 vs 8). Significant improvement in dysphagia was similar in both groups (14/21 radiology vs 14/20 endoscopy, p = 0.82). There was no significant difference in median survival after stenting (135 vs 116 days, p = 0.98), or major 30 day complications defined as perforation, recurrent dysphagia or death (5 in both groups). Conclusion: Direct vision endoscopic SEMS placement was as effective as radiological guidance for dysphagia palliation at our institution, with a similar mortality and complication rate. This provides further evidence for the role of direct vision endoscopic SEMS placement in palliation of malignant dysphagia. Reference: Wilkes EA et al . Insertion of expandable metallic stents in esophageal cancer without fluoroscopy is safe and effective: a 5 year experience. Gastrointest Endosc. 2007 May;65:923–9 Disclosure of Interest: None Declared.